Differences in seed properties and germination between native and introduced populations of Triadica sebifera. (24th October 2019) - Zhang, Jialiang; Siemann, Evan; Tian, Baoliang; Huang, Wei; Ding, Jianqing
Abstract: Aims: Seeds of many invasive plants germinate more quickly than those of native species, likely facilitating invasion success. Assessing the germination traits and seed properties simultaneously for introduced and native populations of an invasive plant is essential to understanding biological invasions. Here, we used Triadica sebifera as a study organism to examine intraspecific differences in seed germination together with seed characteristics. Methods: We measured physical (volume, mass, coat hardness and coat thickness of seeds) and chemical (crude fat, soluble protein, sugar, gibberellins [GA] and abscisic acid [ABA] of kernels) properties of T. sebifera seeds collected in 2017 from 12 introduced (United States) populations and 12 native (China) populations and tested their germination rates and timing in a greenhouse experiment in China. Furthermore, we conducted an extra experiment in the United States using seeds collected in 2016 and 2017 to compare the effects of study sites (China vs. United States) and seed collection time (2016 vs. 2017) on seed germination. Important Findings: Seeds from the introduced range germinated faster than those from the native range. Physical and chemical measurements showed that seeds from the introduced range were larger, had higher GA concentrations and GA:ABA ratio, but lower crude fat concentrations compared to those from the native range. There were no significant differences in seed mass, coat hardness and coat thickness or kernel ABA, soluble protein or sugar concentrations between seeds from introduced vs. native ranges. Germination rates were correlated between United States and China greenhouses but germination rates for populations varied between collection years. Our results suggest that larger seeds and higher GA likely contribute to faster germination, potentially facilitating T. sebifera invasion in the introduced range.